Find the general solution to the given system:
dx/dt=x+2y
dy/dt=2x+y
Let us find the general solution to the given system:
"\\begin{cases}\n\\frac{dx}{dt}=x+2y\\\\\n\\frac{dy}{dt}=2x+y\n\\end{cases}"
The first equation of the system is equivalent to "y=\\frac{1}{2}(\\frac{dx}{dt}-x)". Then "\\frac{dy}{dt}=\\frac{1}{2}(\\frac{d^2x}{dt^2}-\\frac{dx}{dt})". Put these in the second equation of the system. We have the following differential equation:
"\\frac{1}{2}(\\frac{d^2x}{dt^2}-\\frac{dx}{dt})=2x+\\frac{1}{2}(\\frac{dx}{dt}-x)"
which is equivalent to
"\\frac{1}{2}\\frac{d^2x}{dt^2}-\\frac{dx}{dt}-\\frac{3}{2}x=0"
and to
"\\frac{d^2x}{dt^2}-2\\frac{dx}{dt}-3x=0"
Its characteristic equation "k^2-2k-3=0" is equivalent to "(k+1)(k-3)=0", and thus has the solutions "k_1=-1" and "k_2=3."
Therefore, "x(t)=C_1e^{-t}+C_2e^{3t}".
Then "\\frac{dx}{dt}=-C_1e^{-t}+3C_2e^{3t}" and
"y=\\frac{1}{2}(\\frac{dx}{dt}-x)=\\frac{1}{2}(-C_1e^{-t}+3C_2e^{3t}-(C_1e^{-t}+C_2e^{3t}))=-C_1e^{-t}+C_2e^{3t}" .
Consequently, the system has the general solution:
"\\begin{cases}\nx(t)=C_1e^{-t}+C_2e^{3t}\\\\\ny(t)=-C_1e^{-t}+C_2e^{3t}\n\\end{cases}"
Comments
Dear Maria, please use the panel for submitting a new question.
Solve the following system of linear equations dx/dt=2x+y+e' dy/dt=3x+y+3e'
Leave a comment